2017
DOI: 10.1111/tri.13010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk in patients receiving organ transplantation: a national cohort study

Abstract: Although organ transplantation is the definitive treatment for end-stage organ failure, the post-transplant outcomes can be substantially influenced by cardiovascular complications. A national cohort study was performed to estimate risks of cardiovascular diseases in those with heart, lung, kidney, and liver transplantation. This cohort study consisted of 5978 solid organ transplantations identified using the Taiwan National Health Insurance Database. Cardiovascular and mortality risks in transplant recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Importantly, micro- and macrovascular cardiovascular co-morbidities are common in SOT, notably in kidney and heart transplant recipients[ 30 , 31 ]. First, patients are dependent on polypharmacy with a substantial risk of progressive atherosclerosis, notably calcineurin inhibitors and steroids[ 2 , 32 , 33 ].…”
Section: Macro- and Microvascular Complications In Diabetes Mellitus In General And In Sot In Particularmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, micro- and macrovascular cardiovascular co-morbidities are common in SOT, notably in kidney and heart transplant recipients[ 30 , 31 ]. First, patients are dependent on polypharmacy with a substantial risk of progressive atherosclerosis, notably calcineurin inhibitors and steroids[ 2 , 32 , 33 ].…”
Section: Macro- and Microvascular Complications In Diabetes Mellitus In General And In Sot In Particularmentioning
confidence: 99%
“…But a national cohort study from Taiwan showed that even renal transplant recipients still have a twofold higher annual cardiovascular mortality than the general population. The study also included heart, lung, and liver recipients and demonstrated that SOT recipients were at an approximately threefold risk of developing any type of vascular disease[ 30 ].…”
Section: Macro- and Microvascular Complications In Diabetes Mellitus In General And In Sot In Particularmentioning
confidence: 99%
“…It remains unclear whether this is caused by the transplantation itself or a sequel of the underlying disease or an effect of the immunosuppressive medication. Nevertheless, available data indicate that patients after SOT are at high risk for thromboembolic complications [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent solid organ transplantation (SOT) are at higher risk of developing cardiovascular complications such as atrial fibrillation (AF) and venous thromboembolism (VTE) compared to the general population [1,2]. The cumulative incidence of new onset AF within 36 months after kidney transplantation is 7.3% [3].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological interaction between the heart and the kidneys, also known as the cardio-renal syndrome (CRS), often occurs in heart failure and is associated with deterioration of renal function, as well as worse prognosis of therapy and quality of life. Considering the high risk of cardiological burdens and, thus, the possible impaired graft perfusion, there is a discussion about whether there are a validity and chance for graft durability and how high the risk of postoperative complications will be [5, 6]. Prospective and retrospective studies showed a significant improvement in cardiac function after kidney transplantation [7, 8] even in cases of pronounced cardiac failure [911].…”
Section: Introductionmentioning
confidence: 99%